Go Story: Design and Evaluation Educational Mobile Learning Podcast using Human Centered Design Method and Gamification for History - Biabdillah, Fajerin; Tolle, Herman; A. Bachtiar, Fitra (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
Technological developments, especially in the field of education, can help students learn more effectively and help the learning process. The learning method used in high school for history learning still uses conventional methods. The use of this conventional method often experiences problems such as students being less motivated in learning. One of the solutions proposed in this article is to design an android-based learning media that can support the activities of the learning process named go-story. Interface design for students as application users and (UI/UX) based on human centered design methodology and the concept of gamification. The human centered design approach and the concept of gamification will be used in the analysis and design process to maximize the usability and engagement of the application. The application will be implemented and tested on students to measure its effectiveness. The trials that have been carried out show the results of improvements